Serum Antibodies Against Simian Virus 40 Large T Antigen, the Viral Oncoprotein, in Osteosarcoma Patients - Mazzoni, Elisa; Bononi, Ilaria; Benassi, Maria S.; Picci, Piero; Torreggiani, Elena; Rossini, Marika; Simioli, Andrea; Casali, Maria V.; Rizzo, Paola; Tognon, Mauro; Martini, Fernanda (Frontiers in Cell and Developmental Biology, 2018)
Human osteosarcoma (OS) is a rare human cancer, mostly occurring in children and adolescents. Simian virus 40 (SV40= Macaca mulatta polyomavirus 1) sequences have been detected in different human cancers, including osteosarcoma. SV40 is an oncogenic virus in vivo, whereas it transforms different kinds of mammalian cells, as well as distinct human cell types. SV40 injected in rodents induces tumors of different histotypes, such as bone and brain tumors. Herein, the association between OS and SV40 large T antigen (Tag) was studied by employing indirect ELISAs using synthetic peptides that mimic different epitopes of the SV40 Tag, the viral oncoprotein. Indirect ELISAs were used to detect serum IgG antibodies against this oncogenic virus in samples from OS patients. Controls were sera from healthy subjects (HS) and oncological patients affect by breast cancer (BC), which is not associated with SV40. It turned out that sera of OS patients had a higher prevalence of SV40 Tag antibodies, 35%, compared to HS, 20% and BC, 19%, respectively. The different prevalence of SV40 Tag antibodies revealed in OS vs HS and vs BC is statistically significant with P<0.05 and P<0.01, respectively. Our immunological data indicate a significantly higher prevalence of antibodies against SV40 Tag epitopes in serum samples from OS patients compared to HS and BC, the controls. These results suggest an association between OS and SV40 Tag, indicating that this oncogenic virus may be a cofactor in OS development.